Медвежонок Паддингтон здесь и сейчас: [рассказы] / Майкл Бонд - Бонд Майкл (Медвежонок Паддингтон, 2010)
Экземпляры: ф. 3 (20111025) / Инвентарный номер: 97498 / Цена: 225.16 / Авт.знак: Б 81 / ГРНТИ: 17.82 / ББК: 84(4Вел)